Podmiotowe uwarunkowania męskości, kobiecości i androgynii - Lipińska-Grobelny, Agnieszka (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The 1960’s view of gender role orientation held that masculinity and femininity were at opposite ends of the same continuum. Bem challenged this concept by suggesting that masculinity and femininity were actually separate continuums, allowing individuals to endorse both characteristics. Bem described four categories of gender: sex-typed individuals, androgynous individuals, undifferentiated individuals and cross-sex-typed individuals. The authoress of this article conducted researches, delivering five techniques: IPP by Kuczyńska, NEO-FFI by Costa & McCrae, PTS by Strelau & Zawadzki, SD by Ray and MSS by Merrill & Reid to the group of 145 persons. The results indicate several significant differences that may be applied to various domains of life for example to the procedure of recruitment and selection.